Tikopia Collected: Raymond Firth and the Creation of Solomon Islands Cultural Heritage, Elizabeth Bonshek (2017) Collecting in the South Sea: The Voyage of Bruni d'Entrecasteaux 1791‐1794, Bronwen Douglas, Fanny Wonu Veys and Billie Lythberg (eds) (2018) Resonant Histories: Pacific Artefacts and the Voyages of HMS Royalist 1890‐1893, Alison Clark with Eve Haddow and Christopher Wright (2019). Issue 2 (1st December 2021) - Quanchi, Max
Review of: Tikopia Collected: Raymond Firth and the Creation of Solomon Islands Cultural Heritage, Elizabeth Bonshek (2017)Canon Pyon: Sean Kingston Publishing, 222 pp., ISBN 978 1 90777 439 3 (hbk), £60Collecting in the South Sea: The Voyage of Bruni d'Entrecasteaux 1791‐1794, Bronwen Douglas, Fanny Wonu Veys and Billie Lythberg (eds) (2018)Leiden: Sidestone Press, 381 pp., ISBN 978 9 08890 574 2 (pbk), €60 Resonant Histories: Pacific Artefacts and the Voyages of HMS Royalist 1890‐1893, Alison Clark with Eve Haddow and Christopher Wright (2019)Leiden: Sidestone Press, 272 pp., ISBN 978 9 08890 629 9 (pbk), €55